Brivaracetam: review of its pharmacology and potential use as adjunctive therapy in patients with partial onset seizures [Corrigendum] - Mumoli L; Palleria C; Gasparini S; Citraro R; Labate A; Ferlazzo E; Gambardella A; De Sarro G; Russo E (Dove Medical Press, 2015)
Brivaracetam: review of its pharmacology and potential use as adjunctive therapy in patients with partial onset seizures [Corrigendum] Mumoli L, Palleria C, Gasparini S, et al. Drug Des Devel Ther. 2015;9:5719–5725.   The authors advise several errors in the paper that are corrected in Corrigendum. View the original article by Mumoli et al.